Pathogenetic substantiation of surgical treatment of recurrent inguinal hernia. - Bilіanskyі L. S.; Svіsenko O. V.; Netesa, S. I. (Medicni Perspektivi, 2014)
Research purpose was to investigate tissue reactions on implantation of polypropylene mesh, processed with collagen, after plastic surgery of experimental defect in rats in preperitoneal prosthesis localization. Research was performed in two experimental groups. Group 1 – in 17 rats an experimental defect of anterior abdominal wall with 3 cm of size with further preperitoneal fixation of the polypropylene mesh of 0,5×1,0 cm size was performed. Group 2 – in 20 rats under analogous conditions preperitoneal fixation of polypropylene mesh, processed with collagen was performed. Morphological analysis of stages of scar tissue formation in the implantation region in the preperitoneal cavity of rats by stereological characteristics of cellular and fiber structures of connective tissue considering hemodynamic characteristics shows substantial benefits of polypropylene mesh, processed with collagen, during 2 montha after experimental hernioplasty.